Design, synthesis, and evaluation of 1, 4-benzodioxan-substituted chalcones as selective and reversible inhibitors of human monoamine oxidase B. (1st January 2020) - Kong, Zhuo; Sun, Demeng; Jiang, Yanmei; Hu, Yun
Abstract: The inhibition of monoamine oxidase B (MAO-B) could be an effective approach for the treatment of various neurological disorders. In this study, a series of 1, 4-benzodioxan-substituted chalcone derivatives were designed, synthesised and evaluated for their inhibitory activity against human MAO-B (hMAO-B). The majority of these compounds showed inhibitory activity and high selectivity. The most potent compound, ( E )-1-(3-bromo-4-fluorophenyl)-3-(2, 3-dihydrobenzo[ b ][1, 4]dioxin-6-yl)prop-2-en-1-one (22), exhibited an IC50 of 0.026 µM with a selectivity index greater than 1538. Kinetics and reversibility studies confirmed that the representative active compounds acted as competitive and reversible inhibitors of hMAO-B. The enzyme-inhibitor interactions were investigated by molecular docking studies and the rationale was provided. As these potent hMAO-B inhibitors exhibited low neurotoxicity and possessed promising drug-like properties, we believe that these active compounds could be further investigated as potential drug candidates for future in vivo studies.